Analysis of risk factors for endometrial neoplasia as a method for supplementation of indications for D&C in postmenopausal women with uterine bleeding - Znojek, Wojciech; Wilczyński, Jacek R.; Hille, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2007)
Objectives: A diagnostic dilemma exists regarding whether D&C is an obligatory procedure during every hospitalization caused by recurrent uterine bleeding. The decision could be supported by consideration of risk factors obtained from patient’s medical history and clinical examination. Design: The aim of the study was to answer whether analysis of risk factors for endometrial neoplasia could supplement indications for D&C in a group of postmenopausal women with uterine bleeding. Materials and methods: The study group consisted of n=154 postmenopausal women hospitalized between 2000 and 2004 in the Gynaecology Dept. of 5th WSKP in Cracow, and subjected to D&C because of uterine bleeding. Retrospective analysis of data extracted from medical charts and pathological examination was based on Pearson’s linear correlation, linear regression, OR and ROC analysis as well as logistic regression model. Results: Logistic regression revealed that the most important risk factors for endometrial neoplasia were: weight ≥70 kg (OR=3.9), positive history of hypertension (OR=2.0), values of diastolic blood pressure ≥85 mmHg (OR=3.2), age of menopause ≥52 years (OR=2.6), age ≥60 years (OR=2.3) and no HT use (OR=2.0). The chance for endometrial neoplasia combined for all risk factors was OR=5.34 (p<0.0005). Conclusion: Analysis of risk factors indicates patients with the greatest probability of endometrial neoplasia and influences the more accurate targeting of D&C procedure to postmenopausal women with uterine bleeding.